1978
DOI: 10.1680/iicep.1978.2715
|View full text |Cite
|
Sign up to set email alerts
|

The Elasto-Plastic Analysis of Imperfect Cylinders.

Abstract: A finite difference formulation is presented for the large deflexion elasto-plastic analysis of initially imperfect thin cylinders subjected to axial compression and external pressure. The elasto-plastic rigidities of the shell are calculated using a rigorous multi-layer approach, and the governing equations are solved in an incremental form using dynamic relaxation. Complete load-deflexion curves (which include response after the attainment of peak load) have been obtained for various loadings and shell geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been found that a single half-wave initial deflection along a cylinder with different values of L/D would produce a significantly different strength (Harding 1978). Here, L and D are the length and diameter of the pipesectional stub-column, respectively.…”
Section: Stub-columns Of Pipe-shaped Section Subjected To Pure Comprementioning
confidence: 99%
“…It has been found that a single half-wave initial deflection along a cylinder with different values of L/D would produce a significantly different strength (Harding 1978). Here, L and D are the length and diameter of the pipesectional stub-column, respectively.…”
Section: Stub-columns Of Pipe-shaped Section Subjected To Pure Comprementioning
confidence: 99%
“…DRM can use the virtual mass and kinetic damping, so as to avoid the situation that computational cost of EQSA depends on the small size of the model, and the viscous damping coefficient depends on the analysis experience. The application of DRM in the static analysis of structures began in the 50th and 60th of the last century [17][18][19], and its application scope gradually expanded in recent years [20][21][22], and recently it was often used in the analysis of tension structures [3,23,24]. However, it is less common in the application and analysis of strainsoftening structures.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter which determines the onset of this type of instability generally is the thickness of the section which, if below a specific threshold, causes the curling of the sheet metal: this kind of buckling strongly depends on the geometrical imperfections of the structure. They can be generated by different phenomena and they are also related to the manufacturing process of the component [16][17][18][19][20][21][22]. The geometric imperfections in the components play a fundamental role in the design: for example a bridge, whose thorough evaluation and implementation in the FEM software allows a correct estimation force-displacement diagram of the component [23].…”
Section: Introductionmentioning
confidence: 99%